Comparing clinical bladder diaries and recalled patient reports for measuring lower urinary tract symptoms in the symptoms of Lower Urinary Tract Dysfunction Research Network (LURN). Issue 8 (6th September 2022) - Flynn, Kathryn E.; Wiseman, Jonathan B.; Helmuth, Margaret E.; Smith, Abigail R.; Bradley, Catherine S.; Cameron, Anne P.; Henry Lai, H.; Kirkali, Ziya; Kreder, Karl J.; Geynisman‐Tan, Julia; Merion, Robert M.; Weinfurt, Kevin P.; et al.
Abstract: Purpose: Bladder diaries are a key source of information about lower urinary tract symptoms (LUTS); however, many patients do not complete them as instructed. Questionnaire‐based patient‐reported outcome measures (PROMs) are another option for reporting LUTS but may have recall bias. We assessed the strength of the associations between PROMs and a 3‐day bladder diary. Materials and Methods: Symptomatic adults from 6 tertiary care sites completed a 3‐day paper bladder diary and 3‐, 7‐, and 30‐day electronic PROMs. We assessed the linear associations between mapped pairs of diary variables and responses to PROM items using biserial and polyserial correlation coefficients with 95% confidence intervals. Results: Of 290 enrolled participants, 175 (60%) completed the bladder diary as instructed and at least one corresponding PROM. Linear associations were strongest between the diary and 3‐day recall of daytime frequency ( r = 0.75) and nighttime frequency ( r = 0.69), followed by voids with urgency sensations ( r = 0.62), and an item reporting any incontinence ( r = 0.56). Linear associations between bladder diary and specific incontinence variables (e.g., stress, urgency) were low to negligible (ranging from r = 0.16–0.39). Linear associations were consistent across the 3‐, 7‐, and 30‐day recall periods. Conclusions: Missing and unusable bladder diary data were common, highlighting the patient burden associated with this method of data collection. A questionnaire‐based PROM is a reasonable alternative to a diary for reporting voiding frequency and may offer an easier option for reporting some symptoms.